2019
DOI: 10.1080/19420862.2019.1688616
|View full text |Cite
|
Sign up to set email alerts
|

Development of a quantitative relationship between CAR-affinity, antigen abundance, tumor cell depletion and CAR-T cell expansion using a multiscale systems PK-PD model

Abstract: The development of mechanism-based, multiscale pharmacokinetic–pharmacodynamic (PK-PD) models for chimeric antigen receptor (CAR)-T cells is needed to enable investigation of in vitro and in vivo correlation of CAR-T cell responses and to facilitate preclinical-to-clinical translation. Toward this goal, we first developed a cell-level in vitro PD model that quantitatively characterized CAR-T cell-induced target cell depletion, CAR-T cell expansion and cytokine release. The model accounted for key drug-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 39 publications
3
101
0
Order By: Relevance
“…95 A second example of the application of mechanistic modeling to IO is the quantitative modeling of chimeric antigen receptor T cell therapies. 96,97 Agent-based and individual-based simulations are increasingly used for this application, with these simulations being, of course, spatially resolved in their outputs. 98 This does, of course, increase their computational cost.…”
Section: Mathematical Modeling Approaches To Translation In Oncologymentioning
confidence: 99%
“…95 A second example of the application of mechanistic modeling to IO is the quantitative modeling of chimeric antigen receptor T cell therapies. 96,97 Agent-based and individual-based simulations are increasingly used for this application, with these simulations being, of course, spatially resolved in their outputs. 98 This does, of course, increase their computational cost.…”
Section: Mathematical Modeling Approaches To Translation In Oncologymentioning
confidence: 99%
“…Since the year 2011, there have been rapid developments in the field of immunotherapy, and a range of immunocheckpoint inhibitors (ICIs) have been approved for a range of metastatic cancers, including malignant melanoma, lung, kidney, and bladder cancers [1][2][3][4][5]. In recent years, the clinical trial results of genetically engineered immune cells, including chimeric antigen receptor T-cell (CAR-T), TCRengineered T-cell (TCR-T), chimeric antigen receptor natural killer cell (CAR-NK) and more, in the treatment of hematological tumors have also been encouraging [6][7][8]. Immunotherapy has nowadays developed into a new and promising therapy in addition to surgery, radiotherapy, chemotherapy, and molecular targeted therapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…The high-dose cohort exhibited a significantly higher proliferation rate (ρ), and higher capacity (Cmax) compared to the low-dose cohort (data not shown). Studies also observed limited CAR-T expansion at a low dose (< 5 x 10 7 ) 37,38 , and no CAR-T expansion at very low doses (< 10 6 ) 39 , indicating a potential threshold of dose to assure rapid CAR-T expansion and a steep dose-response curve for CAR-T therapy 2,35,40 .…”
mentioning
confidence: 97%
“…In solid tumors, cancer cells are often spatially restricted 34 , providing poor antigen accessibility to CAR-T cells. CAR-T cells have to extravasate into the tumor bed, migrate toward the tumor cells, contact, and then engage the tumor cells 7,35 . Differences in tissue accessibility and delivery rate for CAR-T cells may account for large variability on proliferation rate constant (ρ) between two solid tumor trials ( Fig 4B).…”
mentioning
confidence: 99%
See 1 more Smart Citation